ENGLISH AND HILIGAYNON : PERCEPTION OF ENGLISH TEACHERS ABOUT USING TRANSLANGUAGING - Kuning, Dewi Sri; Haq, Astrina Nurul (Universitas Muhammadiyah Metro, 2024)
Understanding teachers' views concerning Translanguaging is expected to be the best way to overcome linguistic barriers in English classes. This research investigates English teachers' perceptions of using translanguaging methods (English and Hiligaynon) when teaching English subjects in ESL classes. The research method used was descriptive qualitative, with the participants being grade 7 teachers at the junior high school level at Capiz National High School, Philippines. This research instrument is an interview, and data was collected by conducting semi-structured interviews via video call via Facebook Messenger. The data analysis technique for this research uses thematic data analysis. The research results show that teachers perceive translanguaging as a valuable tool for learning English. It not only enhances comprehension but also promotes cognitive development, student confidence, and participation in the classroom. In conclusion, teachers view translanguaging positively in countries where English is a second language when teaching English subjects. Translanguaging promises enhanced communication, cognitive development, inclusive learning, literacy development, and knowledge transfer across disciplines in English language classrooms.